Using learning technology for social studies as a resilient media during the pandemic outbreak - Sholihah, Aprilia Melinda; Umamah, Izza Syarifah; Vierza, Meqqi Fabbio; Marsida, Refki (Universitas Negeri Malang, 2023)
The covid-19 pandemic has almost been experienced in all corners of the world in the last two years. The impact is no exception and also affects the activities of students, workers, or the community in general. However, the existing obstacles do not make humans surrender to that conditions. In fact, with these conditions make everyone compete in creating innovations to support learning activities. This study explores student resilience efforts in dealing with the covid-19 pandemic through learning media as a supporting application in online learning. A conventional literature review was used to elaborate on the research problem. This study found that using learning technology media can make people's and students’ lives resilient during the Covid-19 pandemic. Students found themselves more flexible and encouraged to participate in learning processes. As a result, they could learn effectively in social studies materials provided on the online platform.